Prevalensi rs1998076 dan Hubungannya dengan Alopesia Androgentik pada Populasi Indonesia: Studi Pilot - Erick Sidarta; Mikella Kesya Wie; Giovani Evangelista Alfonsius (Jurnal Biomedika dan Kesehatan, 2026)
Background Androgenetic alopecia (AGA) is the most common form of progressive hair loss. AGA is a polygenic disorder characterized by variability in age of onset, severity, and pattern. Genome-wide association studies (GWAS) have shown that the variant rs1998076 at locus 20p11 may increase risk in Asian and European populations. Association studies of AGA and genetic risk are limited in the Indonesian population. Methods We conducted a cross-sectional pilot study (January-August 2025) in Jakarta, Indonesia, recruiting 100 participants (50 AGA cases and 50 controls). Clinical AGA status was determined by the physician. Anthropometric data, including height, weight, blood pressure, and smoking history, were obtained through measurement and a questionnaire. Genotyping of rs1998076 was performed using allele-specific PCR, and Sanger sequencing was used to validate the results. Results The genotype distribution for rs1998076 was AA (24%), GG (37%), and AG (39%). The allele frequencies for rs1998076 were A (0.435) and G (0.565). However, AGA was not significantly correlated with the rs1998076 genotype (p > 0.05) in multivariate models, although the GG and AG genotypes tended to be associated with a higher risk of AGA than the AA genotype. Conclusions In this pilot study, rs1998076 was not significantly associated with AGA, although the GG genotype showed a non-significant trend toward higher odds. Clinical factors (age, male sex, higher BMI, and hypertension) were correlated. Larger, well-powered studies are needed to clarify the role of rs1998076 in Indonesians.